Quality attributes during 160 days refrigerated shelf life of a smoked, fully cooked sausage formulated with a nitrite containing pork preblend - Collins, Ashley (Kansas State University, 2015)
Pork preblends held for 0, 4 or 7 d were formulated into smoked sausages and analyzed for cook yield, instrumental external color, pH, salt content, proximate analysis, Warner-Bratzler shear force (WBSF), thiobarbituric acid reactive substances (TBARS), sensory analysis and purge percentage during 0, 110, 131 and 160 d display at an average 2.65 °C under fluorescent lighting. One preblend × day of display interaction was found for b* values. On display d 0, preblend d 7 was more yellow (P < 0.05) than preblend d 0 and 4; however, no differences (P > 0.05) were found for any preblends on d 110 or 160. On display d 131, preblend d 0 was more (P < 0.05) yellow than preblend d 4 but similar (P > 0.05) to preblend d 7. There was no preblend effect (P > 0.05) on any of the other attributes measured. Display day did not affect (P > 0.05) purge, pH, proximate analysis, WBSF, juiciness, saltiness or off-flavor. For color, a* and saturation index values decreased (P < 0.05) and L* increased (P < 0.05) between d 0 and 110 as well as d 110 and 131, while L*, a*, a*/b* ratio and saturation index values were similar (P > 0.05) from d 131 to 160. Hue angle value decreased from d 0 to 110 but was similar for the remaining display. A reduction (P < 0.05) in a*/b* ratio was shown from d 0 and 110 (average 0.85) to d 131 and 160 (average 0.78). There was a reduction in salt content by 0.43% and an increase in TBARS values by 0.46 mg malonaldehyde/100 g sample from d 0 compared to d 110, 131 and 160 (P < 0.05). Inconsistent differences were found for sensory panel traits bite and flavor intensity and a reduction in mouthfeel coating was found from d 0, 110 and 131 compared to 160 (P < 0.05). Therefore, preblending could be implemented without any detrimental outcome on quality or sensory attributes of skinless smoked sausage; however, as day of display increases product may become lighter, less red and more oxidized.
Keywords: Extended shelflife; Fluorescent lighting; Mechanically separated turkey; Nitrite; Pork preblend; Precooked smoked sausage; Food Science (0359)